An Examination of Elementary School Teachers' Awareness of Learning Disabilities - Chaudhary, Renu; Mathur, Anshu; Prabavathy, M. (Journal of Neonatal Surgery, 2025)
Learning disabilities are a big challenge in elementary education, with teachers needing specialized knowledge and awareness to identify them early and treat them effectively. This research seeks to determine the awareness of elementary school teachers regarding learning disabilities, specifically in identifying symptoms, adjusting instructional approaches, and providing support to students with learning challenges. The study utilizes a mixed-method design using a structured questionnaire to collect information from 450 elementary school teachers who were selected using stratified random sampling. Statistical methods like regression and ANOVA were utilized to examine the data. The results vary in the degree of awareness among teachers depending on variables like age, level of teaching experience, level of education, and special education training received earlier. Though a vast number of respondents had received training in special education, inconsistencies existed in their capacity to differentiate learning disabilities from academic difficulties. The research emphasizes the importance of overall professional development programs, focused training modules, and policy interventions to fill knowledge gaps and improve inclusive education practices. Enhancing teacher awareness and capability in managing learning disabilities is essential to create a supportive and equitable learning environment that allows all students to achieve their full potential.